'Nutrimune®' and immune defence against pathogens in the gastrointestinal and upper respiratory tracts: evaluation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006. (30th January 2017) - ,; Turck, Dominique; Bresson, Jean‐Louis; Burlingame, Barbara; Dean, Tara; Fairweather‐Tait, Susan; Heinonen, Marina; Hirsch‐Ernst, Karen‐Ildico; Mangelsdorf, Inge; McArdle, Harry J; Naska, Androniki; Neuhäuser‐Berthold, Monika; et al.
Abstract: Following an application from H.J. Heinz Supply Chain Europe B.V., submitted for authorisation of a health claim pursuant to Article 14 of Regulation (EC) No 1924/2006 via the Competent Authority of the Netherlands, the EFSA Panel on Dietetic Products, Nutrition and Allergies (NDA) was asked to deliver an opinion on the scientific substantiation of a health claim related to 'Nutrimune ® ' and immune defence against pathogens in the gastrointestinal (GI) tract and upper respiratory tract (URT). The food 'Nutrimune ® ' (a pasteurised cow's skim milk fermented with Lactobacillus   paracasei CBA L74) which is the subject of the health claim is sufficiently characterised. The Panel considers that immune defence against pathogens in GI tract and URT is a beneficial physiological effect. One human intervention study from which conclusions can be drawn showed an effect of 'Nutrimune ® ' on immune defence against pathogens in the GI tract and the URT, and the results from one animal study could support an effect of 'Nutrimune ® ' on defence against pathogens in the GI tract. However, there were inconsistencies in the reporting of the process and criteria used for the diagnosis of URTI in the human intervention study, the results of this study have not been replicated, and no evidence was provided for a plausible mechanism by which 'Nutrimune ® ' could exert the claimed effect in vivo in humans. The Panel concludes that the evidence provided is insufficient to establish a cause and effect relationship between the consumption of 'Nutrimune ® ' and immune defence against pathogens in the gastrointestinal and upper respiratory tracts. Abstract : This publication is linked to the following EFSA Supporting Publications article: http://onlinelibrary.wiley.com/doi/10.2903/sp.efsa.2017.EN-1267/full